Correction: A luminescent bimetallic iridium(iii) complex for ratiometric tracking intracellular viscosity. Issue 32 (10th April 2018) - Liu, Fengyu; Wen, Jia; Chen, Su-Shing; Sun, Shiguo
Abstract : Correction for 'A luminescent bimetallic iridium(iii ) complex for ratiometric tracking intracellular viscosity' by Fengyu Liu et al., Chem. Commun., 2018, 54, 1371–1374.